A Study on Students Learning Strategies and Self-efficacy in Speaking I Class in ELESP of Sanata Dharma University - Lelita, Yohana Vita (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2016)
Speaking skill is a skill that is judged first than other skills by someone in many languages. This perspective is the underlying reason why ELESP students are demanded to have good speaking ability. Having a good speaking ability will also give them many other benefits. Based on the researchers personal experiences as the first semester student and experiences of doing micro teaching in Speaking I class, it was found that some ELESP students speaking ability was not good enough. This study aims to find out the language learning strategies ELESP students applied to improve their speaking ability and the use of those strategies in relation to the students self-efficacy by distributing questionnaire and conducting interview.